Crime and punishment - "Dostoevsky, Fyodor" (New Delhi, 2017)
Gripped by anxiety, the impoverished, handsome, and intelligent Rodion Raskolnikov has isolated himself from everyone. Preoccupied with his own contemplations, he becomes conscious of his fears. ?I want to attempt a thing like that and am frightened by these trifles,? he thought, with an odd smile. ?Hm . . . yes, all is in a man?s hands and he lets it all slip from cowardice, that?s an axiom.? After much introspection, Raskolnikov murders an old pawnbroker?for the betterment of the society?and escapes unnoticed. But will he be able to escape his own conscience? An exceptional psychological drama, Fyodor Dostoevsky?s Crime and Punishment deftly delves into the mind of a young man who commits a crime, laying bare his mental anguish and moral dilemmas. Having undergone several film adaptations, the novel continues to remain a literary sensation.
Keywords: English fiction